2020
DOI: 10.1055/a-1108-1892
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Left Ventricular Diastolic Dysfunction Using Cardiac Magnetic Resonance Imaging: Comparison of Volume-Time Curves Derived from Long- and Short-Axis Cine Steady-State Free Precession Datasets

Abstract: Purpose To evaluate the diagnostic performance of diastolic function parameters derived from long-axis (LAX) planimetry compared with short-axis (SAX) volumetry in cardiac magnetic resonance imaging. Materials and Methods Cine steady-state free precession (SSFP) datasets of 15 healthy participants (8 young and 7 middle aged) and 25 patients with echocardiographically proven diastolic dysfunction (9 mild, 9 moderate, and 7 severe) were retrospectively included. Volume-time curves for assessing left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These suggest that peak filling time and peak filling rate can be used as useful CMR indicators for diastolic dysfunction. This is consistent with multiple studies that have found that a lower peak filling rate and a longer time to peak filling rate are useful indicators of diastolic dysfunction on CMR [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…These suggest that peak filling time and peak filling rate can be used as useful CMR indicators for diastolic dysfunction. This is consistent with multiple studies that have found that a lower peak filling rate and a longer time to peak filling rate are useful indicators of diastolic dysfunction on CMR [5,6].…”
Section: Discussionsupporting
confidence: 92%
“…This could be attributed to several reasons as follows: (1) TTPF across different stages of diastolic dysfunction should be considered. Schaafs, L. A et al 20 established that, in time/volume curves analysis, TTPR increased with the progression of diastolic dysfunction, whereas it decreased in healthy participants suffering from severe diastolic dysfunction when restrictive LV lling occurs; (2) TTPF cut-off differs depending on the data 17,[20][21][22] since choosing a TTPF cut-off value to assess for the dynamic change of left ventricular relaxation remains challenging.…”
Section: Discussionmentioning
confidence: 99%
“…VTCs and their first derivative were subsequently analysed using a semi-automated script in MATLAB® (MathWorks, Natick, Massachusetts, USA, version R2009a) in accordance with prior publications. 21 A spline algorithm was implemented to generate a smoothed VTC with a time interval of 1 ms. 22 All curves were normalized to the maximal end-diastolic volume (EDV) at t = 0. Figure 1 shows VTC and first derivative from segmented as well as CRT sequences of a patient with normal diastolic function as well as of a patient with grade 1 diastolic dysfunction.…”
Section: Quantitative Analysis Of Volume-time Curvesmentioning
confidence: 99%